Joint laxity and hip rotation in normal children and in those with congenital dislocation of the hip. - Carr, A; Jefferson, R; Benson, M (1993)
We measured the range of rotation in both hips of 397 normal children and in the unaffected hip of 135 children with unilateral congenital dislocation of the hip. Both groups were assessed for generalised joint laxity. Joint laxity was more common in normal children with an internally centred arc of hip rotation than in normal children with a neutral or an externally rotated arc. The children with congenitally dislocated hips had significantly more joint laxity than did the control group and significantly more of them had an internally centred arc of hip rotation. We suggest that the lax joint capsule fails to mould away the neonatal anteversion of the femoral neck during the first few months of life.